A Study of the warehousing system of the Central Refrigerated Warehousing Div. Food Terminal, Inc. - Concepcion, Socorro O.; Fabic, John S.; Ocreto, Ma. Josefina L.; Panis, Michael M.; Tan, Hera G. (College of Engineering, 1987)
This is a study on the present operations of the Central Refrigerated Warehouse (CRW) of the Food Terminal, Inc. The CRW is basically a service entity which offers its refrigerated storage facilities consisting of chillers, freezers and blast freezers to the public. The present system of CRW was documented, from the organizational set-up to the different storage procedures and up to the different materials handling equipments. Problem areas existing in the present system were then pinpointed. The problems that came out from the study include the absence of a quality control officer, faulty office layout, swapping of stored commodities, abandonment of stored goods, unavailability of storage space when demanded and the presence of rodents inside the storage areas. The problems were then analyzed using the cause and effect technique of analysis. Such an analysis revealed those problems which were isolated cases and those which were interlinked with others. Recommendations were then made to these problems by making the system fit into the recommended solutions and not by finding solutions that would fit into the present system. In the course of the cause and effect analysis, other problems arose which include finding the optimum number of of forklifts to put into service, the optimum chiller and freezer mix and the lack of forecasting in the present system. Only the plans of solutions to these problems were made using the following modelling techniques; Queuing, Linear Programming and Forecasting (Winter's Method). This study has made it possible for us to integrate all the concepts, theories we have learned in our earlier IE courses in the observation, analysis and evaluation of the present operations of the Central Refrigerated Warehouse.